2009
DOI: 10.1021/jf804005w
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography−Mass Spectrometry (GC−MS) Characterization of Volatile Compounds in Quality Vinegars with Protected European Geographical Indication

Abstract: The volatile composition of 26 premium quality vinegars belonging to three different protected geographical indications (traditional balsamic vinegar of Modena, balsamic vinegar of Modena, and sherry vinegar) has been characterized by means of a solid-phase extraction (SPE) gas chromatography-mass spectrometry GC-MS method. Among the about 90 quantified compounds, short-chain fatty acids, furanic compounds, enolic derivatives, and some esters were found to discriminate the samples as a consequence of differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 22 publications
8
79
0
1
Order By: Relevance
“…The content of neryl acetate found for the older TBVM-extravecchio vinegars could be a discriminant parameter for this type of vinegars from the rest, as well as the content of ethyl acetate for Sherry vinegars in order to differentiate them from traditional balsamic vinegars (Table 3). A large number of esters were identified in vinegar samples, in agreement with Durán Guerrero et al (2007) and Chinnici et al (2009) who studied the volatile composition in different types of vinegars. Due to the fact that esters result from the fermentation of alcohols or by the reaction of acids with alcohols during aging (Durán Guerrero et al, 2007), the content of short-chain esters was significantly higher in VJ and VR (vinegars from an alcoholic matrix), especially ethyl valerate, ethyl 2-methyl butanoate, ethyl propanoate and ethyl isovalerate, in agreement with .…”
Section: Anovasupporting
confidence: 85%
See 2 more Smart Citations
“…The content of neryl acetate found for the older TBVM-extravecchio vinegars could be a discriminant parameter for this type of vinegars from the rest, as well as the content of ethyl acetate for Sherry vinegars in order to differentiate them from traditional balsamic vinegars (Table 3). A large number of esters were identified in vinegar samples, in agreement with Durán Guerrero et al (2007) and Chinnici et al (2009) who studied the volatile composition in different types of vinegars. Due to the fact that esters result from the fermentation of alcohols or by the reaction of acids with alcohols during aging (Durán Guerrero et al, 2007), the content of short-chain esters was significantly higher in VJ and VR (vinegars from an alcoholic matrix), especially ethyl valerate, ethyl 2-methyl butanoate, ethyl propanoate and ethyl isovalerate, in agreement with .…”
Section: Anovasupporting
confidence: 85%
“…Some of the studied compounds have been previously identified in wine vinegars (Callejón et al, 2008b;Chinnici et al, 2009;Zeppa, Giordano, Gerbi, & Meglioli, 2002), but 39 tentatively identified volatile compounds have not been previously reported in vinegars from this origin ( Table 2). Several of these 39 compounds have been previously identified in grapes, wines and grape distillates (CavenQuantrill & Buglass, 2007;De Torres, Díaz-Maroto, Hermosín-Gutiérrez, & Pérez-Coello, 2010;Lukic et al, 2010;Márquez, Castro, Natera, & García-Barroso, 2008;Nasi, Ferranti, Amato, & Chianese, 2008;Sonni, Natali, Riponi, & Chinnici, 2006), even in Sherry wines (Campo, Cacho, & Ferreira, 2008;Ruiz, Zea, Moyano, & Medina, 2010) while others are thought to derive from wooden casks (De Rosso, Cancian, Panighel, Dalla Vedova, & Flamini, 2009;Vichi et al, 2007).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Colombard wines were stored under the same conditions, and also by Cejudo- Bastante et al (2011) who studied Chardonnay wines stored under light and dark conditions. Moreover, other authors (Marrufo-Curtido et al 2012;Chinnici et al 2009;Piva et al 2008) found that furfural and other furanic compounds were more abundant in vinegars derived from a thermal treatment (traditional balsamic vinegar of Modena).…”
Section: Volatile Compositionmentioning
confidence: 99%
“…3) Refer to Flavor & fragrances [6]. 4) Not detected. * These compounds were tentatively identified by MS library data (Wiley 275K, Hewlett-Packard Co., Bellefonte, PA, USA …”
Section: 서 론 국내 식품소비에 있어서 생산량 기준 국민 다소비 식품 품목 순위를 살펴보면 식생활의 편리성을 추구하는mentioning
confidence: 99%